Lingering Effects of Prenatal Alcohol Exposure on Basal and Ethanol-Evoked Expression of Inflammatory-Related Genes in the CNS of Adolescent and Adult Rats - Doremus-Fitzwater, Tamara L.; Youngentob, Steven L.; Youngentob, Lisa; Gano, Anny; Vore, Andrew S.; Deak, Terrence (Frontiers in Behavioral Neuroscience, 2020)
Emerging data suggest that alcohol’s effects on central inflammatory factors are not uniform across the lifespan. In particular, prenatal alcohol exposure (PAE) significantly alters steady-state levels of neuroimmune factors, as well as subsequent reactivity to later immune challenge. The current experiment investigated developmental sensitivities to, and long-lasting consequences of PAE on ethanol-evoked cytokine expression in male and female adolescent and adult rats. Pregnant dams received either ad libitum ethanol liquid diet (2.2% GD 6 – 8; 4.5% GD 9 – 10; 6.7% GD11-20; 35% daily calories from ethanol) or free-choice access to a control liquid diet and water. At birth, offspring were fostered to dams given free-choice access to the control liquid diet. Pups then matured until mid-adolescence (postnatal day [PD] 35) or adulthood (PD90), at which time they were challenged with either a binge-like dose of ethanol (4 g/kg; intragastrically) or tap water. During intoxication (3 h post-ethanol challenge), brains and blood were collected for assessment of neuroimmune gene expression (RT-PCR) in hippocampus, amygdala, and PVN, as well as for blood ethanol concentrations (BEC) and plasma corticosterone levels. Results revealed that rats challenged with ethanol at either PD35 or PD90 generally exhibited a characteristic cytokine signature of acute intoxication that we have previously reported: increased Il-6 and IkB expression, with decreased Il-1 and Tnf gene expression. With a few exceptions, this pattern of gene changes was observed in all three structures examined, at both ages of postnatal ethanol challenge, and in both sexes. While few significant effects of PAE were observed for ethanol-induced alterations in cytokine expression, there was a consistent (but nonsignificant) trend for PAE to potentiate expression of Il-6 and IkB in all groups except adult females. Although these data suggest that later-life ethanol challenge was a far greater driver of inflammatory signaling than PAE, the current results demonstrate PAE resulted in subtle long-term alterations in expression of many key neuroinflammatory factors associated with NF-B signaling. Such long-lasting impacts of PAE that may engender vulnerability to later environmental events triggering neuroinflammatory processes, such as chronic ethanol exposure or stress, could contribute to heightened vulnerability for PAE-related deficits.